TRAINER RANGKAIAN CONTROL MENGGUNAKAN SISTEM FORWARD REVERSE PADA MOTOR LISTRIK 3 PHASE SEBAGAI MEDIA PEMBELAJARAN DI JURUSAN TEKNIK LISTRIK POLITEKNIK KOTABARU - M. Ashar Tahir; Muhammad Irsan B (UNM Journal of Technology and Vocational, 2024)
The forward reverse circuit is an electric motor control circuit whose function is to provide current to the electric motor or elmot. So that the electric motor can rotate to move forward and backward to move a machine.. The aim of this research is to determine the design, working methods and test results on a 3 phase electric motor forward reverse circuit.The data collection method for this research is observation, namely collecting information from observations or proving the truth of a research design being carried out, the literature study method looking for theoretical references that are relevant to the problem in accordance with the writing of the final assignment, the experimental method is carrying out an experiment to observe the process and The results can then be drawn to conclusions and the waterfall method is a design development model where each stage is carried out sequentially from top to bottom.The results of this study obtained a design by selecting tools and materials for the forward reverse circuit on a 3 phase electric motor. Electric current, obtained from the forward system circuit in the R phase 05.65 A, S phase 06.28 A and T phase 06.09 A and the voltage obtained in the R to S phase 396.5 V, S to T phase 400.3 V and the T to R phase is 387.5 V and the power produced is 811.1278 watts and the speed produced by a 3 phase electric motor using a forward system circuit is 1284 rpm. Electric current, obtained from the reverse system circuit in the R phase 06.07 A, S phase 05.85 A and T phase 06.02 A and voltage, obtained in the R to S phase 400.5 V, S to T phase 398.8 V and the T to R phase is 389.5 V and the power produced is 815.2452 watts and the speed is produced by a 3 phase electric motor using a reverse system circuit of 1278 rpm.